Cognitive and Communicative Pragmatic Parameters of Intertextuality in Mass Media - Володимир Каленич (Психолінгвістика)
Objective. The main objective of this research is to analyse the cognitive and communicative-pragmatic parameters of intertextuality in modern mediatexts. The article deals with the peculiarities of intertextuality expression in mass media as well as identifies the main varieties of intertexts and considers their role in newspaper articles of the information-analytical weekly “Dzerkalo tyzhnya”.